The Impact of Digital Media on Promoting Health Awareness Campaigns in Public Relations It is a master's thesis in the field of media. - محمد, ڕۆژان محمد محمود محمد; رمضان, آ.د. عمر احمد رمضان (Sulaimani Journal for Humanities, 2025)
The primary aim of the study, entitled “The Effect of Digital Media on Improvement Awareness Campaigns in Public Relations,” is to examine both the positive and negative effects of social media on health‐awareness initiatives among 180 students in the College of Pharmacy at the University of Sulaymaniyah. This descriptive research employs a quantitative methodology: all 180 participants completed a structured questionnaire, and the resulting data were collected for analysis. Among the most notable results of the research shown under the influence of digital media, health awareness campaigns have had a significant impact on the research sample, their familiarity with the various types of health awareness campaigns through digital media is very high and this influence is evident across all five health science disciplines. Additionally, the level of importance, effectiveness, and trust in the dissemination of health awareness campaigns via digital media among the students of the College of Pharmacy at the University of Sulaimani is notably high.
Keywords: Impact; Digital Media; Improvement; Public Relations Campaigns